2020
DOI: 10.1111/cbdd.13745
|View full text |Cite
|
Sign up to set email alerts
|

N4‐benzyl‐N2‐phenylquinazoline‐2,4‐diamine compound presents antibacterial and antibiofilm effect against Staphylococcus aureus and Staphylococcus epidermidis

Abstract: Staphylococcus aureus and Staphylococcus epidermidis are the main agents involved with implant-related infections. Their ability to adhere to medical devices with subsequent biofilm formation is crucial to the development of these infections. Herein, we described the antibacterial and antibiofilm activities of a quinazoline-based compound, N 4-benzyl-N 2-phenylquinazoline-2,4-diamine, against both biofilm-forming pathogens. The minimum inhibitory concentrations (MIC) were determined as 25 µM for S. aureus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…However, this effect was greater in benzyl compounds (A) than in naphthalene compound (B), which may be due to its smaller structure and thus greater penetration into the parasite. Also, in various studies, the role and effect of benzyl-containing compounds on various microorganisms and parasites have been confirmed [ [26] , [27] , [28] , [29] ], as in our study, the benzyl derivative showed an ability of over 80% in eliminating Toxoplasma tachyzoites. The main proposed mechanism of action by benzyl compounds may be impaired macromolecular biosynthesis and cell death.…”
Section: Discussionsupporting
confidence: 84%
“…However, this effect was greater in benzyl compounds (A) than in naphthalene compound (B), which may be due to its smaller structure and thus greater penetration into the parasite. Also, in various studies, the role and effect of benzyl-containing compounds on various microorganisms and parasites have been confirmed [ [26] , [27] , [28] , [29] ], as in our study, the benzyl derivative showed an ability of over 80% in eliminating Toxoplasma tachyzoites. The main proposed mechanism of action by benzyl compounds may be impaired macromolecular biosynthesis and cell death.…”
Section: Discussionsupporting
confidence: 84%
“…Escober et al demonstrated that the nuclear factor-kappa B inhibitor N-[3,5-Bis(trifluoromethyl) phenyl]-5-chloro-2-hydroxybenzamide at sub-MIC of 0.0313 μg/mL can inhibit the initial cell attachment and biofilm formation of vancomycin-resistant S. aureus strain VRS1 in a dose-dependent manner [68] . The sub-MICs of other antimicrobial compounds, such as N-nonyloxypentyl-L-DNJ, N4-benzyl-N-2-phenylquinazoline-2,4-diamine, terpenoid (+)-nootkatone, chitosan, marine steroid siphonocholin, zinc oxide, and silver nanoparticles, are found to be able to inhibit the biofilm formation of diverse S. aureus strains [43] , [46] , [69] , [70] , [71] , [89] .…”
Section: Effects Of Sub-mics Of Antibiotics On S Aureus Biofilm Formationmentioning
confidence: 99%
“…Two compounds were used, a quinazoline derivative (PH100, N 4 -benzyl-N 2 -phenylquinazoline-2,4-diamine) and an 8-hydroxyquinoline derivative (PH157, N-(3,4dichlorophenyl)-8-hydroxyquinoline-5-sulfonamide), synthesized by the 'Pharmaceutical Synthesis Group'. PH100 is described by Dos Reis et al (2020), and PH157 was synthesized according to the protocol described by Joaquim et al (2019). Stock solutions were prepared in DMSO (Sigma-Aldrich) so that when diluted in the assay medium, a maximum DMSO concentration of 2% was obtained.…”
Section: Compoundsmentioning
confidence: 99%